MATACOMYTER - Westman, Bror (Tidsskriftet Antropologi, 1997)
Bror Westman: Mataco Myths Taking a point of departure in Levi-Strauss’ concept of the myth as movement in different ways, the article deals with Mataco myths as they have been recorded by Niels Fock during his field work among the Mataco of Gran Chaco in the northern part of Argentina between 1958 and 1962. The form of this body of myths is seen as one of variation and movement, and the contents are understood as dealing with becoming a human being, a cultural being. The figures Sipilak, the culture hero, and Tokuah, the bungler, play important roles in the myths. They incamate different principles, rule over different domains, create different phenomena, and act in different ways. Also the elements fire, water, air, and earth are dealt with in the myths. The universe of the myths is static, moving however between different levels, and the identities of the figures of the myths change. The myths are variations of each other and tell about the sensuous sides of life. The myths deal with concrete, tangible experience.